LncRNA Malat-1 From MSCs-Derived Extracellular Vesicles Suppresses Inflammation and Cartilage Degradation in Osteoarthritis - Pan, Chongzhi; Huang, Wenzhou; Chen, Qi; Xu, Jiu; Yao, Guoyu; Li, Bin; Wu, Tianlong; Yin, Changchang; Cheng, Xigao (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: Extracellular Vesicles (EVs) derived from hMSCs, have the potential to alleviate cartilage damage and inflammation. We aimed to explore the effects of EVs derived from lncRNA malat‐1-overexpressing human mesenchymal stem cells (hMSCs) on chondrocytes. Material and Methods: hMSCs-derived Extracellular Vesicles (hMSCs-EVs) were identified by transmission electron microscopy and western blot. We used a Sprague-Dawley (SD) rat model of CollagenaseⅡ-induced osteoarthritis (OA) as well as IL-1β-induced OA chondrocytes. Lentiviral vectors were used to overexpress lncRNA malat‐1 in hMSCs. Chondrocyte proliferation, inflammation, extracellular matrix degradation, and cell migration were measured by Edu staining, ELISA, western blot analysis, and transwell assay. Chondrocyte apoptosis was evaluated by flow cytometry, Hoechst 33342/PI Staining, and western blot. Safranine O-fast green (S-O) staining and HE staining were used to assess morphologic alterations of the rat knee joint. Results: hMSCsmalat−1-EVs decreased MMP-13, IL-6, and Caspase-3 expression in IL-1β-induced OA chondrocytes. Moreover, hMSCsmalat−1-EVs promoted chondrocyte proliferation and migration, suppressed apoptosis, and attenuated IL-1β-induced chondrocyte injury. Our animal experiments suggested that hMSCsmalat−1-EVs were sufficient to prevent cartilage degeneration. Conclusion: Our findings show that lncRNA malat-1from hMSCs‐delivered EVs can promote chondrocyte proliferation, alleviate chondrocyte inflammation and cartilage degeneration, and enhance chondrocyte repair. Overall, hMSCsmalat−1-EVs might be a new potential therapeutic option for patients with OA.